Developing smart dumbbells based on iNEMO inertial measurement unit - A - Li, Shiwei. (2013)
In recent years, Inertial Measurement Unit (IMU) has been used in various applications such as flight dynamics, GPS, robots and smart phones. IMU is a combination of accelerometer and gyroscope sometimes also includes magnetometer. With the sensors integrate on a single PCB board, IMU is capable to detect the linear acceleration and orientation changes of the board. In addition, magnet field in vicinity will also be detected. [1] Furthermore, with sensor fusion algorithm, IMU can provide more valuable information such as the absolute orientation of the board in earth frame and the linear acceleration excluding the gravity.